Contribution of select physiological variables to sprint triathlon performance - Papavassiliou, T.; Zacharogiannis, E.; Soultanakis, H.; Paradisis, G.; Dagli, F. P. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of this study was to examine the relationship between select physiological variables and sprint triathlon performance. METHODS: Moderately trained male triathletes (N.=15) performed two graded maximal exercise tests, on a cycle ergometer and a treadmill. Anaerobic capacity was evaluated, on a cycle ergometer and a treadmill. Within two weeks before or after the testing, all triathletes participated in a sprint triathlon race (750 m sea swim, 20 km cycle, 5 km run). RESULTS: The results showed that significant correlations exist between VO2max during cycling (r=-0.811, P<0.05) or running (r=-0.757, P<0.05) and overall triathlon performance. Stepwise multiple linear regression analysis, with triathlon performance as the dependent variable and the physiological measures during running as the independent variables, showed that VO2max (mL/min.kg), Time_CF, CHO_rate @ VT and % body fat yielded the best prediction of performance (R2=0,912). When only the physiological variables from cycling were included into the model, the results showed that VO2max (mL/min), VO2max (mL/min.kg) and PFmax (rpm) explained 88% of the variation in sprint triathlon performance. CONCLUSIONS: Our data indicate that overall race time for moderately trained triathletes, competing over the sprint distance can be accurately predicted from maximal laboratory tests.